2020
DOI: 10.1177/0735633120967318
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Influence of Achievement Emotions for Student Learning in MOOCs

Abstract: Massive Open Online Courses (MOOCs) have become a popular tool for worldwide learners. However, a lack of emotional interaction and support is an important reason for learners to abandon their learning and eventually results in poor learning performance. This study applied an integrative framework of achievement emotions to uncover their holistic influence on students’ learning by analyzing more than 400,000 forum posts from 13 MOOCs. Six machine-learning models were first built to automatically identify achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…On one aspect, empirical evidence seemed to suggest the positive effects of negative emotions on online learning outcomes (e.g., Hilliard et al, 2020). On the other aspect, recent research found that positive achievement emotions had a negative influence on online learners' learning outcomes (Liu et al, 2021). Therefore, there has been little agreement on whether achievement emotions could be beneficial or detrimental to online learning outcomes.…”
Section: Roles Of Achievement Emotions In Online Learning Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…On one aspect, empirical evidence seemed to suggest the positive effects of negative emotions on online learning outcomes (e.g., Hilliard et al, 2020). On the other aspect, recent research found that positive achievement emotions had a negative influence on online learners' learning outcomes (Liu et al, 2021). Therefore, there has been little agreement on whether achievement emotions could be beneficial or detrimental to online learning outcomes.…”
Section: Roles Of Achievement Emotions In Online Learning Outcomesmentioning
confidence: 99%
“…Online learners could improve their performance because they have experienced positive achievement emotions (Parker et al, 2021). Nevertheless, some students feeling positive emotions have performed poorly in online learning (Liu et al, 2021). To date, the effects of achievement emotions on online learning performance have still not been systematically reviewed.…”
Section: Performancementioning
confidence: 99%
“…However, these existing studies simply explore the positive and negative emotions [32], while learners could have more complex achievement emotions, such as confusion, boredom, shame, which could affect the learning outcome [37]. A deeper understanding of the reasons of how students think and feel regarding the course could help to timely identify students at risk and help improve their engagement [21].…”
Section: Comment Analysismentioning
confidence: 99%
“…10 Some methods for establishing MOOC prediction model are proposed in the literature, including k-nearest neighbor (K-NN), logistic regression, decision tree (DT), random forest (RF), and support vector machine (SVM). [11][12][13][14] This paper proposes an intelligent algorithm combining DT, SVM, and simulated annealing (SA) to obtain the best classification accuracy and decision rules for university students' satisfaction with the wisdom tree MOOC platform. The SVM has good classification performance and the DT can generate decision rules.…”
Section: Introductionmentioning
confidence: 99%